2020
DOI: 10.1080/09638288.2020.1837264
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of participation restriction over a 9-year period in adults with myotonic dystrophy type 1

Abstract: les innovations en sant e (CR-CSIS), Centre int egr e universitaire de sant e et de services sociaux du Saguenay

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 79 publications
(102 reference statements)
1
9
0
Order By: Relevance
“…Muscle strength was expressed as the expected muscle strength of healthy individuals based on a French isometric strength normative database using predictive equations taking into consideration age, sex, and weight of the patients 31 . Patients were subjected to a battery of validated functional tests 63, 64 . Timed-up and Go: time to stand up, walk three meters, turn and walk back to sit down on the chair; 10mWT: comfortable walking speed (m/s) along a 10-meter distance; Berg balance scale: 14 items measuring static and dynamic balance (maximum score of 56 indicating no deficit in balance); Pinch strength: measured using a B&L pinch gauge (kg).…”
Section: Methodsmentioning
confidence: 99%
“…Muscle strength was expressed as the expected muscle strength of healthy individuals based on a French isometric strength normative database using predictive equations taking into consideration age, sex, and weight of the patients 31 . Patients were subjected to a battery of validated functional tests 63, 64 . Timed-up and Go: time to stand up, walk three meters, turn and walk back to sit down on the chair; 10mWT: comfortable walking speed (m/s) along a 10-meter distance; Berg balance scale: 14 items measuring static and dynamic balance (maximum score of 56 indicating no deficit in balance); Pinch strength: measured using a B&L pinch gauge (kg).…”
Section: Methodsmentioning
confidence: 99%
“…The ICF component with the highest registered needs was environmental factors , with 880 registrations in total. Environmental factors are considered as barriers or facilitators in relation to activity and participation 11,26 . In the present study, assisted aids and personal assistance was the second most common environmental factor, with 250 registrations in total.…”
Section: Discussionmentioning
confidence: 60%
“…In addition to assisted aids and personal assistance , needs regarding residence and life event transitions were also significant environmental factors in the present study. This is underlined by a study by Raymond et al who found that use of community services for adapted transportation and perception of obstacles in the physical environment and accessibility are predictors for reduced participation 11 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations